Endoscopic Evaluation and Management of Gastrointestinal Bleeding in Patients with Ventricular Assist Devices. (28th February 2012) - Meyer, Marty M.; Young, Scott D.; Sun, Benjamin; Azzouz, Maher; Firstenberg, Michael S.
Abstract : The optimal diagnostic approach and yield for gastrointestinal bleeding (GIB) in patients with ventricular assist devices (VAD) are unknown. We explored the etiology of bleeding and yield of upper and lower endoscopy, balloon-assisted enteroscopy, and video capsule endoscopy in the evaluation of GIB in patients with VADs. Methods . All VAD patients with overt gastrointestinal bleeding and drop in hematocrit from April 1, 2000 to July 31, 2008 were retrospectively reviewed. The endoscopic evaluation of each episode was recorded. Overall yield of EGD, colonoscopy, balloon-assisted, and video capsule endoscopy were evaluated. Results . Thirty-six bleeding episodes occurred involving 20 patients. The site of GIB was identified in 32/36 episodes (88.9%), and the etiology of bleeding was determined in 30/36 cases (83.3%). Five VAD patients underwent VCE. The VCE exams demonstrated a high yield with 80% of exams identifying the etiology of GIB. Endoscopic intervention was successful in 8/9 attempts. No adverse events were recorded. Two patients required surgical intervention for GIB. Conclusion . Upper, lower, video capsule, and balloon-assisted enteroscopies are safe and demonstrate a high yield in the investigation of gastrointestinal bleeding in VAD patients. Medical centers caring for VAD patients should employ a standardized protocol to optimize endoscopic evaluation and intervention.